Comparative in vivo pharmacokinetics study of affeic acid, isoferulic acid and ferulic acid in crude and three different prepared Cimicifuga foetida L. (4th July 2020) - Wu, Yu; Xu, Yan; Yang, Aihua; Shen, Shuijie; Mi, Daguo; Cao, Yongjun; Hua, Zhengying; Min, Lingtian; Li, Weidong
Abstract: Our study investigated the differences in pharmacokinetics of three major components of crude Cimicifuga foetida L. and its fried product and honey‐ and liquor‐prepared products. A rapid and sensitive ultra‐high performance liquid chromatography with tandem mass spectrometry approach was established for determing caffeic acid, isoferulic acid and ferulic acid in rat plasma. The approach has good linearity, precision, accuracy, recovery and stability. Phenolic acid was rapidly absorbed. The times to peak concentration were shorter in the processed group than those for the crude product, with their values of <30 min. The peak concentration values of caffeic acid and isoferulic acid were higher in the crude group than in the processed groups ( p  < 0.05). Area under the curve values of the three phenolics in the crude group were significantly higher than those of the processed groups ( p < 0.05).